Application of epidural anesthesia for cesarean section in a patient with multiple sclerosis: Case report and literature review - Talih, Gamze; Unal Kantekin, Cigdem; Parlak Cikrikci, Aysegul (Annals of Medical Research, 2021)
None
Keywords: Multiple sclerosis; cesarean section; epidural anesthesia.